(3ebGdI GdEScfOQ GdEaQhOjSi jbJaj ajgG QCi GdOjebQGWi OGHjbhQS hSGFQ CMOGK GdadGSaI GdHGbi aj GdYfGjIs - (3GdEScfOQ GdEaQhOjSis
(3ChdgG (B:s
(3bGd (B: (3Ef GdPjf JadSahG ai CeQ GdYfGjI s
(3BNQgG (B:s
(3hPdc Cf GdPi jecf Cf jchf hCf dGjchf gh ehVhY GdCchGf JeJ GdebGdI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/9) s
Keywords: (3GdadSaI hGdefWbs